Agrarian Reform in Historical Perspective, Concept and Implementation - Listyowati Sumanto (Eduvest - Journal of Universal Studies, 2022)
Land reform in a broad sense is called Agrarian Reform, and in a narrow sense it is called Land reform. This study aims to describe Agrarian Reform in the perspective of history, concept and implementation in Indonesia. This type of research uses normative legal research, is descriptive. The data were analyzed qualitatively. Drawing conclusions using deductive logic. The results show that Landreform has experienced a history of policy change. Agrarian Reform is a restructuring of the structure of control, ownership, use and utilization of land that is more equitable through asset management and is accompanied by structuring access for the prosperity of the Indonesian people. The substance of Presidential Regulation Number 86 of 2018 concerning Agrarian Reform places more emphasis on aspects of asset management and land access by conducting land redistribution, land legalization, and community empowerment compared to aspects of handling agrarian disputes and conflicts as a source of land ownership inequality. Therefore, it is necessary to regulate proportionally regarding the handling of disputes and conflicts. After the issuance of Law no. 11 of 2020 concerning Job Creation, the land object for Agrarian Reform is undergoing expansion.